Group dynamics are associated with weight loss in the behavioral treatment of obesity. (14th July 2015) - Nackers, Lisa M.; Dubyak, Pamela J.; Lu, Xiaomin; Anton, Stephen D.; Dutton, Gareth R.; Perri, Michael G.
Abstract : Objective: To assess whether group dynamics are associated with weight loss, session attendance, and self‐monitoring adherence after 6 months of lifestyle intervention for obesity. Methods: Women with obesity ( N  = 125; mean ± SD BMI = 37.84 ± 3.94 kg/m 2 ; age =  51.99 ± 10.81 years) participated in a 24‐week group‐based lifestyle weight loss intervention and achieved a weight loss of 9.13 ± 7.15 kg after 6 months. Participants reported their perceptions of group conflict, avoidance, engagement, social support, and attraction at the end of treatment. Multiple regression with forward selection assessed which group dynamic variables were associated with weight loss, attendance, and adherence. Results: Greater perceived group conflict was associated with smaller weight losses ( β  = 1.833, P  = 0.044) and lower attendance ( β  = −2.313, P  = 0.002) and adherence rates ( β  = −2.261, P  = 0.030). Higher group attraction was associated with higher attendance rates ( β  = 0.051, P  = 0.039). The association between perceived conflict and weight change was mediated by attendance and adherence ( P  = 0.019). Conclusions: Findings demonstrate that group dynamics associate with weight loss outcomes, attendance, and adherence. Addressing conflicts and fostering acceptance among group members may promote success in group‐based lifestyle interventions for obesity.